THE FREQUENCY OF USE OF COMBINATIONS OF ANTIHYPERTENSIVE DRUGS IN PATIENTS WITH DIFFICULT-TO-CONTROL HYPERTENSION ON THE BACKGROUND OF BIOFEEDBACK AND PACED BREATHING AND HEART RATE VARIABILITY - Tymoshenko, O. S.; Yabluchansky, M. I.; Bilchenko, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
The frequency of administration of combinations of antihypertensive drugs and its changes at different stages of observation was studied in 60 patients with difficult-to-control arterial hypertension (DTCAH) (32 men and 28 women) aged 59.0 ± 9.4. All patients were randomly divided into two subgroups: biofeedback (BFB) in the loop of paced breathing (PB) and heart rate variability (HRV) (33 patients) – basic subgroup, subgroup of comparisons (27 patients). Determined that patients with DTCAH in the subgroup of patients with the BFB in the loop of PB there has been a reduction of four-component antihypertensive therapy to three-component and in the subgroup of comparisons the frequency of the appointment of a four-component therapy was increased. At the same time, it was found that the addition of drug therapy with regular BFB sessions in the loop of PB contributed to the potentiation of the antihypertensive effect in patients with DTCAH. It is concluded that the BFB in the loop of PB and HRV can be used as a technology to improve the efficiency of control of blood pressure in patients with DTCAH.